Nutritional ecology: Understanding the intersection of climate/environmental change, food systems and health - Raiten, Daniel J.; Combs, Gerald F. (International Food Policy Research Institute, 2019)
The global imperative is complex: to support stable, healthy dietary patterns that are environmentally friendly (particularly regarding GHGE) and are acceptable across a range of culturally diverse settings. Ultimately, the purpose of agriculture is to support human health and well-being. Translating available knowledge about the relationships of diet and health depends on developing evidence-informed guidelines and specific health targets. Following those guidelines and meeting those targets will depend on having sustainable food supplies. The challenge is to accomplish that goal in the face of CEC (Aleksandrowicz et al., 2016; Horgan et al., 2016; Péneau et al., 2017; Perignon et al., 2017; Ridoutt et al., 2017). CEC is exerting profound effects on current and potentially future efforts to feed and care for a hungry planet. Its impacts on land/marine food systems are clear and significant. The effects of CEC are not limited to food systems; they also threaten health. Nutrition serves as the biological variable of health that links these effects. We have laid out a conceptual framework for why and how the elements of the nutrition ecology must be integrated into efforts moving forward to sustain global food production and improve human health in the face of CEC. This approach will facilitate the development of effective responses to one of the most compelling challenges of our time.